Penerapan Model Story Telling untuk Meningkatkan Penghayatan Ajaran Kitab Suci pada Siswa SMPS Katolik Ratu Damai Waibalun - Maria Susana Mboti; Hendrikus Febrianto Fernandez (Jurnal Nakula : Pusat Ilmu Pendidikan, Bahasa dan Ilmu Sosial, 2026)
This research is motivated by students' low appreciation of the teachings of the Bible, which is evident in their lack of understanding of spiritual values ​​in everyday life. The purpose of this study is to describe the application of the storytelling model in increasing appreciation of the teachings of the Bible among eighth-grade students of Ratu Damai Waibalun Junior High School. This study uses a qualitative approach with a descriptive research type. The research subjects consisted of seventh-grade students and Catholic religious teachers. Data collection techniques were carried out through observation, in-depth interviews, and documentation. Data were analyzed through data reduction, data presentation, and drawing conclusions. The results show that the application of the storytelling model can create a more lively, interesting, and meaningful learning atmosphere, so that students more easily understand and appreciate the teachings of the Bible. In addition, storytelling encourages students' emotional involvement, increases personal reflection, and helps students connect teaching values ​​with real experiences. The implications of this study indicate that the storytelling model can be an effective and contextual learning strategy in fostering a deeper appreciation of students' spiritual values.